Comparative study of fine needle aspiration cytology and tru-cut biopsy in the diagnosis of breast lesions - Andola, Sainath K.; Masgal, Meenakshi; Nigudgi, Shantling; Pathan, Tabassumnaz; Deshpande, Gururaj (International Journal of Research in Medical Sciences, 2024)
Background: Breast carcinoma is one of the most researched cancers across the world. FNAC is often used as a first priority investigation in patients with breast lump. Tru-cut biopsy is useful in preoperative knowledge of prognostic parameters with the help of IHC markers ER, PR, Her2 neu. The technique is reliable, simple and reproducible which can be used even in resource poor countries like India. To analyze the sensitivity, specificity, positive predictive values and negative predictive values and the diagnostic accuracy (efficacy) of fine needle aspiration cytology and trucut biopsy. Methods: The study included 82 patients presenting with palpable breast lesions. All patients underwent FNAC followed by Tru-cut biopsy under ultrasound guidance. ER, PR, HER2 Neu, cytokeratin immunostaining was done in malignant cases. The data collected analysed statistically. Results: The sensitivity, specificity, PPV, NPV of FNAC were 96.61 %, 95.65 %, 98.28%, 90.91% respectively and that of trucut biopsy were 100%, 100%, 100%, and 100 % respectively. Conclusions: Out of total 82 patients, maximum no of cases (57) were duct carcinoma accounting 69.50% on FNAC and Tru-cut biopsy. IHC was done in all carcinomas. Maximum (46 cases) were luminal type. The present study emphasizes that tru-cut biopsy can serve as confirmative diagnostic tool over FNAC and provides information regarding prognostic factors and treatment modalities based on IHC markers.